Desenvolvimento e avaliação de scaffold oriundo de tendão descelularizado - Santos, Alex De Lima [UNIFESP] (2021)
Introduction: The use of scaffolds has considerably advanced in recent years, mainly in soft tissue injuries with large damage to the original tissue. In a way to optimize the tissue-scaffold integration, the research of decellularized scaffold is growing. Objective: This paper aimed to produce and evaluate decellularized tendon scaffolds from biomechanical, microscopic, macroscopic, and in vivo perspectives in rabbits. Methods: Thirty-six tendons from adult New Zealand rabbits were used: 11 were used as controls, and 25 were decellularized (Scaffold). The groups were subjected to histological, biomechanical, and macroscopic analyses, and the scaffold was submitted to an additional in vivo evaluation. In this evaluation, we have used eight additional rabbits in the experimental model of a bilateral rotator cuff tear and insertion of the scaffold on one side and the contralateral used as a control. Results: The scaffold showed alteration in the architecture; we have noted it with the increment of intra/inter-fascicular distance, and no change in the parallelism of ECM. And a substantial loss of nuclear material, we have established it in the reduction and disorganization of remaining nuclear material. In the biomechanical analysis, no significant differences were found after analysing the ultimate tensile load, stiffness, and elongation at the ultimate tensile load. During the in vivo evaluation was noted progressive cell infiltration in the scaffold. Conclusion: The evaluated decellularization protocol made a tendon scaffold, maintained the most important biomechanical characteristics, and permitted progressive tissue integration, when it was used in an augmentation function.